TEMPORAL DEVELOPMENT OF THE 1999 INTRUSIVE EPISODE IN THE EYJAFJALLAJöKULL VOLCANO, ICELAND, DERIVED FROM INSAR IMAGES - Pedersen R.; Sigmundsson F. (My University, 2006)
Eyjafjallajökull volcano, located in southern Iceland, is characterized by its quiet nature. Only about a handful of earthquakes associated with the volcanic system had been detected prior to the 1990s. Earthquake swarms did, however, occur in 1994 and 1999. Here we investigate the spatio-temporal evolution of a magmatic intrusion associated with the 1999 earthquake swarm via analysis of produced surface deformation. A series of interferometric synthetic aperture radar (InSAR) images, spanning various periods of the intrusion, show that in 1999 surface deformation occurred mainly on the southern flanks of the volcano. The deformation amounts to more than 20 cm of range change. Inverse modeling resolves the deformation source to be a sill intrusion at 6.3 km depth. Sill opening was up to 1 m and the total intruded volume amounts to ~0.03 km3. The InSAR data display a migration of the center of deformation through time, enabling us to create time-dependant sill-opening models. Furthermore, we investigate the spatio-temporal distribution of earthquakes and find that the distribution supports the InSAR derived model and additionally provides indications for a possible site of a feeder channel. Magmatic flow-rate estimates indicate an initial intrusion rate of 4–6 m3/s, declining over a few weeks.
Keywords: ICELAND; VOLCANO; INTRUSION; SILL; SEISMIC SWARM; DEFORMATION; INSAR